2014
DOI: 10.1111/vcp.12139
|View full text |Cite
|
Sign up to set email alerts
|

Association between excess body weight and urine protein concentration in healthy dogs

Abstract: Clinicopathologic abnormalities consistent with ORG were absent from overweight/obese dogs in this study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 14 publications
1
12
0
Order By: Relevance
“…An obesity-related glomerulopathy is well described in human beings (Praga and Morales, 2006) and experimentally-induced obesity in dogs results in glomerular lesions (Henegar et al, 2001). However, a recent study did not find any relationship between obesity and proteinuria in client-owned dogs; 20 dogs were overweight or obese, and all had UPC values <0.2 (Tefft et al, 2014). Most of the dogs in this study had an ideal BCS, which could have hindered the ability to identify a relationship between obesity and HTG or proteinuria.…”
Section: Discussionmentioning
confidence: 94%
“…An obesity-related glomerulopathy is well described in human beings (Praga and Morales, 2006) and experimentally-induced obesity in dogs results in glomerular lesions (Henegar et al, 2001). However, a recent study did not find any relationship between obesity and proteinuria in client-owned dogs; 20 dogs were overweight or obese, and all had UPC values <0.2 (Tefft et al, 2014). Most of the dogs in this study had an ideal BCS, which could have hindered the ability to identify a relationship between obesity and HTG or proteinuria.…”
Section: Discussionmentioning
confidence: 94%
“…A recent study on 20 overweight/obese dogs and 22 ideal bodyweight control dogs found no effect of obesity on the level of proteinuria/microalbuminuria, concluding that clinicopathological abnormalities consistent with obesity-related glomerulopathy are absent. 34 However, this contrasts with the significant reduction in proteinuria seen after weight loss in dogs with naturally occurring obesity. 35 Larger scale studies, including renal biopsies, are necessary to further assess the effect of canine obesity on proteinuria.…”
Section: Discussionmentioning
confidence: 95%
“…Because of the small sample size, the effect of BCS on proteinuria in dogs could not be evaluated. A recent study on 20 overweight/obese dogs and 22 ideal bodyweight control dogs found no effect of obesity on the level of proteinuria/microalbuminuria, concluding that clinicopathological abnormalities consistent with obesity‐related glomerulopathy are absent . However, this contrasts with the significant reduction in proteinuria seen after weight loss in dogs with naturally occurring obesity .…”
Section: Discussionmentioning
confidence: 95%
“…Glomerular lesions have been reported with experimentally induced obesity in dogs, but urinary protein concentration was not quantified for the dogs. In a study that included 6 obese (BCS, 8–9 of 9) client‐owned dogs, none had an increased UPC . Further studies evaluating the relationship between obesity and HTG should be performed to determine whether improved BCS influences the severity of proteinuria seen in markedly obese dogs.…”
Section: Discussionmentioning
confidence: 99%